Comparison of postoperative analgesic efficacy of caudal block versus dorsal penile nerve block with bupivacaine for circumcision in children - Shweta Patel,; Sheetal Shah,; Hiren Parmar, (Universiti Kebangsaan Malaysia, 2015)
Background: Circumcision is a frequently performed surgery in pediatric patient. Objective: Our aim is to compare postoperative analgesia of caudal block versus dorsal penile nerve block (DPNB) and to compare sedation score and complication associated with caudal block and DPNB in children undergoing circumcision. Materials and Methods: This prospective randomized study was performed for more than 50 patients of ASA grade I, aged 3–12 years, scheduled for elective circumcision. Patients were divided into two groups: DPNB for group I and caudal block for group II, using 0.25% 1 mL/kg (2 mg/kg) bupivacaine. Postoperative analgesia was evaluated for 6 hours with the FLACC Pain Scale for five categories: (F) face, (L) legs, (A) activity, (C) cry, and (C) consolability. Sedation was evaluated with Ramsey sedation score. For every child, supplementary analgesic amount and times and probable local or systemic complications were recorded. Results: No significant difference between both the groups was found in mean age, body weight, and surgery duration and sedation scores. Initially, for 2 hours, FLACC pain score was also insignificant; however, on subsequent measurements, a significant difference of FLACC pain score was noted in both the groups. No major complication was found when using either technique. Conclusion: Duration of postoperative analgesia is more in caudal group than that of DPNB. Supplementary analgesic need is also minimized.